A sucessão Jurássica-Eocretácea da bacia do Parnaíba, NE do Brasil: paleoambiente, diagênese e correlação com os eventos magmáticos do Atlântico Central (CAMP). - RABELO, Cleber Eduardo Neri (Universidade Federal do Pará, 2019)
The evolution of the Jurassic-Cretaceous transition (~200 to 100 Ma) in the northern Brazilian basins was marked by expressive paleoenvironmental, paleoclimatic and paleogeographic changes related to the Pangea’s breakup. This event was concomitant with the opening of the Central Atlantic Ocean (ca. 190 Ma) and the installation of large igneous provinces (LIPs) such as the Magmatic Province of the Central Atlantic or CAMP. These events preceded the breakdown of the West Gondwana and, in Brazil, are recorded mainly in the basins of Solimões, Amazonas, and Parnaíba. Extrusion of CAMP basalts occurred only in the Parnaíba Basin related to the Lower Jurassic Mosquito Formation (199, 7 ± 2.45 Ma) generally interbedded with sandstone and mudstone (intertrap deposits), unconformably overlain by the Lower Cretaceous Corda and Pastos Bons formations. Facies and petrographic analysis based on outcrops and drill cores of this succession in the central-west and southeast portions of the Parnaíba Basin revealed thirty-four sedimentary facies grouped in 8 facies associations representing wet desert systems implanted on a basaltic substrate (Mosquito and Corda formations) and of lacustrine systems (Mosquito intertrap deposits and Pastos Bons Formation). The intertrap sandstone is interpreted as fluvial-eolian deposits composed of intensely silicified fine- to coarse-grained sandstone with rounded to subangular grains, granules and pebbles predominantly of volcanic, quartz, and subordinate feldspars. The fluvial channels with subaqueous dunes and sand sheets were incised on the basaltic substrate and flash flood propitiated the mechanical infiltration of clays on the sediments forming coatings over grains. Eolian dunes were adjacent to the fluvial system recorded by fine- to medium-grained sandstone with rounded and frosted grains and exhibiting small- to medium-scale low-angle and tabular cross-stratification. Interdune and pond/shallow lake deposits developed in topographic shoals consist of silicified sandstonemudstone rhythmite with wavy bedding and fine-grained sandstone with adhesion structures. The heat-flow and hydrothermal activity of basalt eruption increasing the devitrification of volcanic clasts releasing silica and propitiating massive eodiagenetic precipitation of chalcedony, megaquartz, poikilotopic zeolite and Fe-Ti oxides reducing the porosity and the permeability precluding the post-Jurassic burial diagenesis. During the Late Jurassic to Early Cretaceous, the decreasing of isotherms and crustal loading induced by the weight of basalt bodies propitiated the implantation of the Corda wet desert system. The desert system consisted of dune field and ephemerous and perennial fluvial channels with preferential migration to the southeast. Dune field deposits consist of fine- to medium-grained sandstone with rounded and frosted grains with smallto medium-scale tabular and tangential cross-stratifications, even parallel stratification and subcritically climbing ripple-cross lamination. Wet interdune deposits consist in fine- to mediumgrained sandstone forming centimetric-scale cycles with tops interpreted as paleosoils indicated by mottled horizons rich in iron oxide-hydroxide, bioturbations, wavy lamination, adhesion structures, and dissecation cracks. The Corda fluvial system probably fed the Pastos Bons lake implanted on the basin depocenter during Early Cretaceous. These fluvial deposits consist predominantly of conglomerates with angular granules and pebbles of basalt, fine- to coarsegrained sandstones with trough and sigmoidal cross-beddings, cross lamination, massive bedding, and subordinate mudstone. Sand sheet deposits are composed of fine- to coarse-grained sandstone with even parallel lamination, low angle cross-bedding, subcritically climbing ripple-cross lamination, adhesion ripples, gutter casts, and load cast structures. The poikilotopic zeolite is represented by laumontite and Ca-stilbite occurring mainly in the dune field deposits. This cementation was produced by the interaction of the fluid that percolated the weathered volcanic substrate. The reactivation of this diagenetic system was triggered by the Cretaceous magmatism (The Post-CAMP Sardinha Formation). This regional heating influenced and accelerating the chemical reactions in an open hydrological diagenetic system with alkaline pH, low-PCO2, K+ depletion, and high Si/Al relation. The eodiagenetic phase of the Corda sandstone was marked by the precipitation of calcite fringes, Ca-stilbite, and mechanical compaction. In contrast, the laumontite was precipitated in high temperatures. This research allowed us to expand our knowledge mainly about: 1) the processes and products linked to the interaction between continental sedimentation and the last magmatic event of the CAMP; 2) the early cementation mechanisms that hindered the burial diagenesis effects on these deposits; and 3) the role of post-CAMP heating in the reactivation of the Cretaceous diagenetic system. This new understanding represents a signature on recognition of the Jurassic-Cretaceous deposits of the Parnaíba Basin, which can be used in the correlation with other basins of the West Gondwana.